Sporna imena naselij v Sloveniji - Geršič, Matjaž (Georitem, 2021)
Settlement names are the type of geographical names or toponyms that people come across most often. In Slovenia, their unification or standardization is handled by the Commission for Standardization of Geographical Names of the Government of the Republic of Slovenia, which is based at the Anton Melik Geographical Institute of the Research Centre of the Slovenian Academy of Sciences and Arts. The Commission operates mainly on the basis of UN resolutions on geographical names, Slovenian orthography and Slovenian legislation on geographical names, and publishes standardized geographical names in standardization documents (such as maps and gazetteers) and online on the Surveying and Mapping Authority of the Republic of Slovenia. There are more than 6,000 settlement names in Slovenia, a fifth of which are disputed for various reasons and should be corrected.The book ('Disputed names of settlements in Slovenia') first discusses basic terms in the field of geographical names, especially settlement names, then describes the methodology for determining disputed settlement name in Slovenia and proposes corrected names of disputed names, and finally presents standardized names on maps at a scale of 1: 1,000,000 and 1:250,000 and in the Register of Geographical Names or REZI, which is the largest database of geographical names in Slovenia.